Sojas integrais tostada pelo vapor e extrusada em rações de poedeiras - Sakomura, N. K.; da Silva, R.; Basaglia, R.; Malheiros, E. B.; Junqueira, O. M. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
An experiment with 400 laying hens Hy Line with 26 weeks of age was conducted to compare the performance of laying hens fed during four cycles of 28 days with diets containing soybean meal (SM) plus soybean oil (SBM+oil), whole extruded soybean (ESB) and whole steam toasted soybean (TSB). A completely design randomized blocks was used, with 10 treatments and five replicates and eight laying hens in each experimental unit. The treatments consisted on the replacement of SBM per ESB and TSB at the levels 0, 25, 50, 75 and 100%; and as control the SBM with or without addition of oil. The results obtained showed that the hens were able to regulate the feed intake to maintain the energy intake only at lower energetic levels, however they tended to over intake energy with the increase of energy levels of the diets. The addition of oil or soybeans in the diets improved feed: gain ratio, however worsened the energy efficiency in relation to the diet without oil. The processing of soybean provided differences on the performance of laying hens and the ESB showed to be superior to TSB. The hens had higher use of the oil added to the soybean meal (SBM + oil) and ESB in relation to TSB. However, the values of AMEn obtained for the ESB were 12% higher, in average, to those determined for the SBM + oil and for the TSB.
Whole steam toasted and extruded soybean on diets of laying hens
Keywords: commercial laying hen; whole-extruded soybean; whole steam toasted soybean nutrition value